Fast-Track Pancreaticoduodenectomy in the Elderly. Issue 3 (March 2017) - Zouros, Efstratios; Liakakos, Theodoros; Machairas, Anastasios; Patapis, Paulos; Tzerbinis, Helen; Manatakis, Dimitrios K.; Papadimitriou-Olivgeris, Matthaios; Dervenis, Christos
It remains uncertain whether enhanced recovery after surgery (ERAS) protocols can be safely implemented for elderly patients, especially after highly complex surgery such as pancreaticoduodenectomy (PD). The present study was designed to assess the feasibility and safety of an ERAS protocol in elderly patients undergoing PD. Starting January 2010 to February 2015, we prospectively collected data from 85 consecutive patients who underwent PD with a fast-track program. Data of patients older and younger than 70 years were compared. Endpoints were morbidity, mortality, readmissions, length of stay, and compliance with ERAS elements. Forty-five patients were less than 70 years old and 40 patients were 70 years of age or older. Both mortality (4.4% vs 5%; P = 1.000) and overall morbidity (33.3% vs 37.5%; P = 0.821) did not differ significantly between the groups. Rates of intervention and relaparotomy were similar in both groups. Length of stay (10 vs 11.8 days; P = 0.099) did not differ significantly between the groups, nor did the readmission rates (6.7% vs 5.0%; P = 0.272). There were no differences in compliance with ERAS elements between groups. An ERAS program seems feasible and can be safely implemented for elderly patients undergoing PD.